Pemberdayaan Masyarakat Dalam Meningkatkan Kepedulian Lingkungan Berbasis Potensi Lokal - Harianto Harianto (JURNAL DAYA-MAS, 2021)
Abstract— In the village of Keras Kulon, Gerih Subdistrict, Ngawi Regency most of the people are farmers. That way most of it is used for processing agricultural land. On the other side of the house, each farmer's family and other families have many courtyards and yards that are quite large and not well-maintained with lots of overgrown plants which originate from planting and as long as they grow by themselves. Therefore, there is still a gap to empower the community, especially for women farmers and female families who are members of the PKK by utilizing existing land in each in the yard or in the yard by cultivating Ginger plants. Ginger cultivation has strategic values both economic and non-economic for the community to provide added value both economically and non-economically as well. Ginger plant cultivation that can easily be done by PKK members on their spare time so that the land in the yard or in the yard of the house will be planted with ginger plants planted on the sidelines and mango plants, jackfruit trees, banana trees and so on. Empowering rural communities through PKK, considering the most active organization in the village for mothers is PKK. This empowerment is to improve environmental awareness based on local potential, and plants according to needs. The community service activities will be held from September to December 2018. At regular PKK meetings scheduled every month in Keras Kulon Village, Gerih District, Ngawi Regency as a community with assistance and assistance methods. Keywords—: Community Empowerment; Environmental Awareness; Local Potential.